Assessing the Impact of Specialist Palliative Care on Healthcare Utilisation at the End of Life Among Patients With Pancreatic Cancer: A Nationwide Register‐Based Cohort Study - Rautakorpi, Liisa; Nåhls, Nelli‐Sofia; Saarto, Tiina; Nuutinen, Mikko; Akrén, Outi; Carpén, Timo (Wiley, 2026)
Introduction
Advanced pancreatic cancer is often a rapidly progressing malignancy causing high symptom burden. The objective of this study was to assess the association of specialist palliative care (SPC) and its timing with healthcare resource utilisation at the end of life.
Methods
This nationwide retrospective study which covers the whole population of Finland included all 1199 patients who died of pancreatic cancer in 2019. Data were obtained from national registries. Patients were categorised into two groups based on the timing of their first contact with SPC: Group I (> 30 days before death), and Group II (≤ 30 days before death or no contact).
Results
Among 1199 patients, 438 (36%) had a SPC contact, and median time from the first contact to death was 51 days. Contact with a SPC occurred > 30 days before death for 22.5% of the patients (n = 270). Having an earlier contact with SPC (Group I) was significantly associated with fewer secondary care hospitalisations (25% vs. 56%, p < 0.001) and fewer emergency department (ED) contacts (50% vs. 61%, p < 0.001) during the last month of life. In addition, patients in Group I were more likely to receive hospital-at-home services (44% vs. 9%, p < 0.001) and to receive care in SPC wards (23% vs. 5%, p < 0.001). Most of the patients died in hospital (56% vs. 79%, p < 0.001), but death in SPC ward (22% vs. 5%, p < 0.001) or at home (19% vs. 13%, p < 0.014) was more likely for patients in Group I.
Conclusion
Lower secondary healthcare utilisation and ED contacts during the last month of life, and higher probability of dying in SPC ward or at home, were observed in patients who had an earlier SPC contact. Integration of SPC in time should be ensured for all patients with advanced pancreatic cancer.